An Exploratory Study of Place Marketing Factors in Albanian Football - Bundo, Julian; Axhami, Mirdaim (European Journal of Economics and Business Studies, 2020)
Beyond the beautiful game, place is another factor in terms of importance for mix marketing. In football industry place is mainly related to the stadium where the football is produced and consumed from the fans of clubs. For football marketers the atmosphere of the stadium that must prevail to make the fans experience unique, remains one of the most important challenges every week of the seasons. Fans around the world tend to have special experiences in the stadiums, not only for the conditions and services but also mainly for the equipment with the latest technology around it. In Albania, poor quality stadiums and their hostile environment is still an obstacle to the development of football. The main purpose of this study is to understand how the place marketing factor affects football fans in Albanian championship. Using a national representative sample of football fans (N=800), we use exploratory factor analysis to analyze place marketing factor, thus exploring dimensions that define football consumption behavior. The analysis results in four factors, which display nuances of the place marketing factor in the football consumption of Albanian fans. Further, ANOVA is used to examine differences between groups.